Protein requirements for Blue-fronted Amazon (Amazona aestiva) growth - Carciofi, A. C. [UNESP]; Sanfilippo, L. F.; de-Oliveira, L. D. [UNESP]; do Amaral, P. P.; Prada, F. (Wiley-Blackwell, 2008)
The objective of this study was to evaluate the protein requirements for hand-rearing Blue-fronted Amazon parrots (Amazona aestiva). Forty hatchlings were fed semi-purified diets containing one of four (as-fed basis) protein levels: 13%, 18%, 23% and 28%. The experiment was carried out in a randomized block design with the initial weight of the nestling as the blocking factor and 10 parrots per protein level. Regression analysis was used to determine relationships between protein level and biometric measurements. The data indicated that 13% crude protein supported nestling growth with 18% being the minimum tested level required for maximum development. The optimal protein concentration for maximum weight gain was 24.4% (p = 0.08; r(2) = 0.25), tail length 23.7% (p = 0.09; r(2) = 0.19), wing length 23.0% (p = 0.07; r(2) = 0.17), tarsus length 21.3% (p = 0.06; r(2) = 0.10) and tarsus width 21.4% (p = 0.07; r(2) = 0.09). Tarsus measurements were larger in males (p < 0.05), indicating that sex must be considered when studying developing psittacines. These results were obtained using a highly digestible protein and a diet with moderate metabolizable energy levels.
Keywords: Amazon; birds; hand rearing; Nutrition; psittacine